2021
DOI: 10.11002/kjfp.2021.28.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive changes of nutritional constituents and antioxidant activities of ginseng sprouts according to the roasting process

Abstract: This study comprehensively investigated the physicochemical properties, nutritional constituents, and antioxidant activity of ginseng sprouts (GS) according to the roasting process. The fatty acid and mineral contents of GS were almost unchanged, but the free amino acid contents decreased. Moreover, ginsenoside contents decreased during the roasting process, whereas total phenolics and flavonoids, Maillard reaction products, phenolic acid and flavonol contents increased. In particular, the contents of ginsenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Kim et al [29] reported that the total phenolic and flavonoid contents of the shoot of ginseng sprouts were higher than those of the root; our results were similar to those of previous studies. The potential antioxidant activity was positively correlated with total phenolic and flavonoid contents [29,33,41,42]. However, our study showed different results depending on the growth period and cultivars.…”
Section: Biological Compounds (Total Phenolic and Flavonoid Contents)supporting
confidence: 92%
See 3 more Smart Citations
“…Kim et al [29] reported that the total phenolic and flavonoid contents of the shoot of ginseng sprouts were higher than those of the root; our results were similar to those of previous studies. The potential antioxidant activity was positively correlated with total phenolic and flavonoid contents [29,33,41,42]. However, our study showed different results depending on the growth period and cultivars.…”
Section: Biological Compounds (Total Phenolic and Flavonoid Contents)supporting
confidence: 92%
“…Phytochemicals such as phenolic acids and flavonoids are widely present in various plants and are known as representative antioxidants derived from natural products [39,40]. Kim et al [29] reported that the total phenolic and flavonoid contents of the shoot of ginseng sprouts were higher than those of the root; our results were similar to those of previous studies. The potential antioxidant activity was positively correlated with total phenolic and flavonoid contents [29,33,41,42].…”
Section: Biological Compounds (Total Phenolic and Flavonoid Contents)supporting
confidence: 91%
See 2 more Smart Citations
“…However, most studies have been conducted on the intact compounds contained in ginseng sprouts and their efficacies, and little information is available on the processing of ginseng sprouts or efficacies of the processed products. Kim et al [10] reported that ginsenoside content decreased whereas total phenolic and flavonoid content increased during the roasting process of ginseng sprouts. Hwang et al [11] investigated the improved antioxidant, anti-inflammatory, and anti-adipogenic properties of hydroponic ginseng fermented by Leuconostoc mesenteroides.…”
Section: Introductionmentioning
confidence: 99%